2022
DOI: 10.1136/neurintsurg-2021-018079
|View full text |Cite
|
Sign up to set email alerts
|

Stroke thrombectomy volume, rather than stroke center accreditation status of hospitals, is associated with mortality and discharge disposition

Abstract: BackgroundFew studies have explored the association between stroke thrombectomy (ST) volume and hospital accreditation with clinical outcomes.ObjectiveTo assess the association of ST case volume and accreditation status with in-hospital mortality and home discharge disposition using the national Medicare Provider Analysis and Review (MEDPAR) database.MethodsRates of hospital mortality, home discharge disposition, and hospital stay were compared between accredited and non-accredited hospitals using 2017–2018 ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The Catalonian stroke system of care during trial enrollment period was centralized in Barcelona metropolitan area, where all thrombectomy‐capable centers were located, with consistent rates of thrombolytic and thrombectomy treatment, little variations in workflow time metrics between centers, 34 and a unique provider of pre‐hospital evaluation (Servei d'Emergències Mèdiques). As compared with other stroke systems of care in the United States, with a wide range of stroke center capabilities according to the Joint Commission, 35 larger variability in time metrics and annually patients volume across centers, 36,37 different locations and travel times between centers, 38 and different EMS providers rendering services in the same areas, direct application of our results should be cautiously considered.…”
Section: Discussionmentioning
confidence: 82%
“…The Catalonian stroke system of care during trial enrollment period was centralized in Barcelona metropolitan area, where all thrombectomy‐capable centers were located, with consistent rates of thrombolytic and thrombectomy treatment, little variations in workflow time metrics between centers, 34 and a unique provider of pre‐hospital evaluation (Servei d'Emergències Mèdiques). As compared with other stroke systems of care in the United States, with a wide range of stroke center capabilities according to the Joint Commission, 35 larger variability in time metrics and annually patients volume across centers, 36,37 different locations and travel times between centers, 38 and different EMS providers rendering services in the same areas, direct application of our results should be cautiously considered.…”
Section: Discussionmentioning
confidence: 82%
“…In cardiology, the difference in PCI outcomes by volume is modest and the trade‐offs continue to be debated 16 . Volumes and years of experience at the operator level do play an important role in EVT for stroke 24,25 . Large‐volume hospitals are more likely to be equipped with dedicated neurocritical units and stroke units, which may independently impact outcomes 41…”
Section: Discussionmentioning
confidence: 99%
“…16 Volumes and years of experience at the operator level do play an important role in EVT for stroke. 24,25 Large-volume hospitals are more likely to be equipped with dedicated neurocritical units and stroke units, which may independently impact outcomes. 41 Despite the relatively higher complexity of stroke care, the current EVT expectations set forth by the Joint Commission are even lower at only 15 procedures/yr (or 30 over 2 years) at both institutional and operator levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study has demonstrated that case volume, rather than accreditation status, is associated with lower mortality and better discharge status. 31 Therefore, the implementation of more TCCs should be strategized, taking into account provider coverage, time of access to the treatment center, and case volume to be served.…”
Section: Challenges and Solutions Prehospital Lvo Detection And Bypas...mentioning
confidence: 99%